2017
DOI: 10.1186/s12884-017-1372-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Both parents should care for babies’: A cross-sectional, cross-cultural comparison of adolescents’ breastfeeding intentions, and the influence of shared-parenting beliefs

Abstract: Background: Many young men and women expect to co-parent their newborn infant. This may have a positive or negative impact on decisions to breastfeed, which is an important health behaviour, influenced by cultural and psycho-social norms. We investigated the relationship between shared parenting, infant feeding beliefs and intentions in male and female (non-parent) adolescents, comparing Nordic countries (Sweden, Norway, Finland) with high breastfeeding rates with others with low rates (Scotland, USA). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…The decision to breastfeed is often considered the mother’s responsibility and is likely determined in the prenatal period. In a cross-sectional survey of male and female adolescents (12–18 years of age, N = 1064), including students in Texas ( n = 170), Swanson and colleagues (2017) found that parenting beliefs and gender norms related to parenting roles influenced breastfeeding intentions. Findings support the need to explore and leverage factors impacting on the breastfeeding intentions of males prior to fatherhood.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to breastfeed is often considered the mother’s responsibility and is likely determined in the prenatal period. In a cross-sectional survey of male and female adolescents (12–18 years of age, N = 1064), including students in Texas ( n = 170), Swanson and colleagues (2017) found that parenting beliefs and gender norms related to parenting roles influenced breastfeeding intentions. Findings support the need to explore and leverage factors impacting on the breastfeeding intentions of males prior to fatherhood.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found (23,29) that breastfeeding outcome is not exclusively in uence by the mother decisions, emphasizing the importance of the role that the partner or father plays, as well as, extended family support (mothers, aunts, etc) and breastfeeding support groups. In the present study, we did not nd any word referring to masculine or paternal gures in the SR of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Both 'instrumental' support, focused on speci c stressors such as worries about the baby, sleep problems and loneliness, and 'emotional' support for the parental role are important. Expectations of 'ideal' parenting roles increasingly appear to emphasise the importance of 'shared parenting' [32]. Practical shared parenting (e.g.…”
Section: Discussionmentioning
confidence: 99%